The Effects of Aging and Environment on Vision - Armstrong, Donald; Marmor, Michael F.; Ordy, J. Mark (Springer US, 1991)
This book derives from a symposium conducted in San Francisco CA, entitled "Environmental Design for Optimum Vision in the Elderly" that was sponsored by the American Aging Association, October 11-12, 1985. Presentations from this symposium comprise the core content of this volume. However, manuscripts have also been accepted from additional authors whose topics and research findings increase the scope and goals of this volume. Previously unpublished data is found in several of the chapters. In addition new data and references have been incorporated at the end of chapters in order to provide a current update of the subject. The broad aims of the papers in this volume were to examine the effects of various environmental factors, long-term occupational hazards, and toxins on basic visual functions in relation to physiological, biochemical, morphological, and pathological alterations in the eye and visual pathways, and centers of the brain. As part of the more specific aims of this volume, the editors have provided the following framework for the specific topics included in this volume: I) Epidemiology, Clinical and Psychophysical Research, II) Ophthalmological, Biochemical, Physiological and Anatomical studies, and III) Environmental Hazards